2007
DOI: 10.1111/j.1365-2389.2007.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic matter chemistry in allophanic soils: a pyrolysis‐GC/MS study of a Costa Rican Andosol catena

Abstract: Soil organic matter (SOM) in allophanic soils is supposed to accumulate due to protection caused by binding to allophane, aluminium and iron. We investigated a catena of allophanic and non-allophanic soils in Costa Rica to determine the effect of such binding mechanisms on SOM chemistry. These soils contain no contribution of black carbon. Molecular characterization of litter, extractable and dispersed organic matter was done by Curie-point pyrolysis-GC/MS. The molecular chemistry of the organic fractions indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
153
2
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 59 publications
8
153
2
8
Order By: Relevance
“…The role of Al-humus complexes in enhancing the resistance of humic substances to microbial decomposition has been demonstrated by incubation experiments (Martin et al, 1966;Juste et al, 1975;Martin et al, 1982;Rasmussen et al, 2006). However, a pyrolysis-GC/MS investigation of soil organic matter in Andosols from Costa Rica did not support the theory of strong chemical protection of plant-derived components through binding to allophane, iron or aluminum (Buurman et al, 2007). Therefore, other processes may be important in SOM sequestration in Andosols.…”
Section: Organic Carbon Accumulation In Andosolsmentioning
confidence: 86%
See 2 more Smart Citations
“…The role of Al-humus complexes in enhancing the resistance of humic substances to microbial decomposition has been demonstrated by incubation experiments (Martin et al, 1966;Juste et al, 1975;Martin et al, 1982;Rasmussen et al, 2006). However, a pyrolysis-GC/MS investigation of soil organic matter in Andosols from Costa Rica did not support the theory of strong chemical protection of plant-derived components through binding to allophane, iron or aluminum (Buurman et al, 2007). Therefore, other processes may be important in SOM sequestration in Andosols.…”
Section: Organic Carbon Accumulation In Andosolsmentioning
confidence: 86%
“…Due to high water retention by micro-aggregates, it is plausible that anaerobic conditions may hinder aerobic decomposers in the aggregate interiors, even under otherwise well-aerated conditions at the soil pedon scale. For example, Buurman et al (2007) reported incorporation of SOM into 10 μm-diamater aggregates that remained saturated with water throughout much of the year, thereby hindering microbial decomposition. As fluid migration is reduced inside the fractal structure of the aggregates, the SOM adsorbed or trapped in these fractal pore structures is less available to microbes and enzymes (Chevallier et al, 2010).…”
Section: Organic Carbon Accumulation In Andosolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furfural (N), is mostly derived from carbohydates, ligno-cellulosic materials, proteins and other aliphatic organic compounds (Bracewell & Robertson, 1984), indicating the presence of rapidly metabolisable organic substances. Acetic acid (K) is preferentially derived from pyrolysis of lipids, fats, and waxes, cellulose, carbohydrates (Bracewell & Robertson, 1984) and represents relatively less-degraded lignocellulose material (Sollins et al, 1996;Buurman et al, 2007). Phenol (Y) is derived from amino acids, tannins and fresh or condensed (humic) lignocellulosic structures (van Bergen et al, 1998;Lobe et al, 2002).…”
Section: Pyrolysis-gas Chromatographymentioning
confidence: 99%
“…Ultimamente, a pirólise associada à cromatografia gasosa/espectrometria de massas (Pi-CG/EM) também tem sido muito utilizada no estudo tanto da MOS quanto de suas SHs (SAIZ-JIMENEZ; DE LEEUW, 1986;SCHNITZER, 1997;LEINWBER;SCHULTEN, 1999), pois permite seu maior detalhamento químico, permitindo distinguir por exemplo, a contribuição de compostos derivados diretamente das plantas e de microorganismos (ALCÂNTARA et al, 2004;BUURMAN et al, 2006;PETERSE;MARTINS, 2007;, complementando assim, as informações obtidas pelas demais técnicas químicas e espectroscópicas citadas anteriormente (STEVENSON, 1994).…”
Section: Introductionunclassified